2002
DOI: 10.1007/s10278-002-0022-7
|View full text |Cite
|
Sign up to set email alerts
|

Workflow Optimization: Current Trends and Future Directions

Abstract: In an attempt to maximize productivity within the medical imaging department, increasing importance and attention is being placed on workflow. Workflow is the process of analyzing individual steps that occur during a single event, such as the performance of an MRI exam. The primary focus of workflow optimization within the imaging department is automation and task consolidation, however, a number of other factors should be considered including the stochastic nature of the workload, availability of human resour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 9 publications
1
40
0
1
Order By: Relevance
“…For medical imaging, user groups (e.g., community practice radiologists and technologists) tend to primarily view innovation from a workflow perspective, while purchaser groups (e.g., radiology and hospital administrators) view innovation primarily from an economic perspective, and influencer groups (e.g., academic radiologists and researchers) often focus on quality. An example of a successful IT innovation which accomplished all three priorities is PACS, which has been shown to improve workflow and productivity, decrease operational costs, and improve quality [16][17][18].…”
Section: Innovation and The End Usermentioning
confidence: 99%
“…For medical imaging, user groups (e.g., community practice radiologists and technologists) tend to primarily view innovation from a workflow perspective, while purchaser groups (e.g., radiology and hospital administrators) view innovation primarily from an economic perspective, and influencer groups (e.g., academic radiologists and researchers) often focus on quality. An example of a successful IT innovation which accomplished all three priorities is PACS, which has been shown to improve workflow and productivity, decrease operational costs, and improve quality [16][17][18].…”
Section: Innovation and The End Usermentioning
confidence: 99%
“…They also note that the introduction of digital modalities have done little to reduce that 0531 shortage. Reiner et al [1], in 2002, also evaluated technologist workflow and identified multiple factors that impact that work flow. Their observations indicated that transition to filmless operations enhanced workflow.…”
Section: Introductionmentioning
confidence: 97%
“…Consequently, the prohibitive costs of imaging devices severely restrict radiology departments from purchasing additional equipment in an effort to enhance patient throughput and reduce waiting times. Hence, improving the efficiency of service delivery process is emerging to be a viable step for radiology departments and a priority of healthcare organizations worldwide (National Research Council, 2009;National Health Services, 2007;Reiner et al, 2002).…”
Section: Introductionmentioning
confidence: 99%